A study of experiential quality, experiential value, trust, corporate reputation, experiential satisfaction and behavioral intentions for cruise tourists: The case of Hong Kong. (June 2018) - Wu, Hung-Che; Cheng, Ching-Chan; Ai, Chi-Han
Abstract: The purpose of this study is to identify the dimensions of experiential quality and investigate the relationships among experiential quality, experiential value (emotional value and functional value), trust, corporate reputation, experiential satisfaction and behavioral intentions perceived by cruise tourists. A multi-dimensional and hierarchical approach is used to examine the relationships between these higher order constructs. Analysis of data from 677 respondents experiencing the cruise tour organized by Bauhinia indicates that the proposed model fits the data well. The results of this analysis contribute to the services marketing theory by providing empirically–based insight into the experiential quality and experiential satisfaction constructs in the cruise industry. This study will assist cruise management in developing and implementing a market-oriented service strategy to achieve a high quality of experiences, enhance cruise tourists' experiential satisfaction and create their favorable future behavioral intentions. Highlights: This study proposed a multi-dimensional and hierarchical model of experiential quality. This study identified the relationships among experiential quality, experiential value, experiential satisfaction and behavioral intentions. A survey of a total of 677 tourists who experienced the cruise tour was conducted in this study. Results helped cruise management to be aware of the importance cruise tourists place on the dimensions of experiential quality.